The Selective SIK2 Inhibitor ARN-3236 Produces Strong Antidepressant-Like Efficacy in Mice via the Hippocampal CRTC1-CREB-BDNF Pathway - Liu, Yue; Tang, Wenqian; Ji, Chunhui; Gu, Jianghong; Chen, Yanmei; Huang, Jie; Zhao, Xinyi; Sun, Yingfang; Wang, Chengniu; Guan, Wei; Liu, Jianfeng; Jiang, Bo (Frontiers in Pharmacology, 2021)
Depression is a widespread chronic medical illness affecting thoughts, mood, and physical health. However, the limited and delayed therapeutic efficacy of monoaminergic drugs has led to intensive research efforts to develop novel antidepressants. ARN-3236 is the first potent and selective inhibitor of salt-inducible kinase 2 (SIK2). In this study, a multidisciplinary approach was used to explore the antidepressant-like actions of ARN-3236 in mice. Chronic social defeat stress (CSDS) and chronic unpredictable mild stress (CUMS) models of depression, various behavioral tests, high performance liquid chromatography-tandem mass spectrometry, stereotactic infusion, viral-mediated gene transfer, western blotting, co-immunoprecipitation and immunofluorescence were used together. It was found that ARN-3236 could penetrate the blood-brain barrier. Repeated ARN-3236 administration induced significant antidepressant-like effects in both the CSDS and CUMS models of depression, accompanied with fully preventing the stress-enhanced SIK2 expression and cytoplasmic translocation of cyclic adenosine monophosphate response element binding protein (CREB)-regulated transcription coactivator 1 (CRTC1) in the hippocampus. ARN-3236 treatment also completely reversed the down-regulating effects of CSDS and CUMS on the hippocampal brain-derived neurotrophic factor (BDNF) system and neurogenesis. Moreover, we demonstrated that the hippocampal CRTC1-CREB-BDNF pathway mediated the antidepressant-like efficacy of ARN-3236. Collectively, ARN-3236 possesses strong protecting effects against chronic stress, and could be a novel antidepressant beyond monoaminergic drugs.